PENGARUH PROGRAM KONSELING DAN TES HIV TERHADAP PENERIMAAN DIRI PASIEN HIV DAMPAKNYA KEPADA KUALITAS HIDUP - Syofyan, Syofyan; Nurliana Nasution; Anto Ariyanto (Universitas Lancang Kuning, 2024)
This study aims to determine whether the influence of the HIV counseling and testing program on self-acceptance in HIV patients has an impact on quality of life. This research uses quantitative methods with verification analysis using the PLS Structural Equational Modeling (SEM) statistical test. The total population in this study was no greater than 100 respondents, the author took 100% of the population of HIV patients who were identified by sources and information at the Simpang Tiga Pekanbaru Community Health Center, 71 people. Thus it can be concluded that there is an influence of the counseling program on self-acceptance of HIV patients, there is an influence of HIV testing on self-acceptance of HIV patients, there is an influence of counseling programs on quality of life, there is an influence of HIV testing on quality of life, there is an influence of quality of life on self-acceptance of HIV patients, quality of life mediates the relationship between counseling programs and HIV patient self-acceptance, quality of life mediates the relationship between HIV testing and self-acceptance of HIV patients at Simpang Tiga Pekanbaru Health Center.